Pelatihan Instalasi Pompa Air dengan Tenaga Surya Bagi Masyarakat Sekitar Politeknik Penerbangan Palembang - Soleh, Asep Muhamad; Setiyo, Setiyo; Sukahir, Sukahir; Parjan, Parjan; Amalia, Direstu; Hasniati, Amalia Resky; Handayani, Ni Putu Heni; Hernando, M. Farizi (Jurnal Pengabdian Kepada Masyarakat, 2024)
Renewable energy is a major issue currently developing in the world. Every country is trying to increase the use of renewable energy for its people. In Indonesia, the government continues to educate the public to reduce the use of energy derived from fossil fuels. Palembang Aviation Polytechnic as a government agency, is trying to educate the public about the use of renewable energy. The implementation of renewable energy outreach is carried out with Community Service as one of the three principles of higher education, in the form of training on installing water pumps using solar power. The participants in this training were students from the Sriwijaya Palembang Aviation Vocational School. The activity was carried out at the Sriwijaya Palembang Talang Betutu Vocational High School. The result of this activity is that participants can install solar panels as a source of solar electricity. All participants can install solar panels. By holding this activity, it is hoped that Indonesia will become the largest user of renewable energy in the world.